Virtual Processor based on Hybrid Processor (Global Journal of Computer Science and Technology, 2019)
This proposal presents a robust method through which virtualization can be optimized by the use of a hybrid processor. The discourse acknowledges that virtualization has become a key constituent of machine processing and efficiency through building virtual machine clusters that can be universally integrated to harness the utilization of hardware computing resources. As observed in low-level computing paradigms, the traditional x86 architecture was only capable of classical trapping to deploy virtualization, yielding para-virtualization. In response, virtual processors based on hybrid processors with hardware-assisted paging enables the handling of foreign Memory Management Unit (MMU) operations and translates the corresponding physical address to actual machine-controlled dynamic addresses, improving memory bound executions as well as the overall output of the HVM. This architecture derives a more powerful utility from the compromised architecture whereby the kernel space while the user space resides in the same privilege ring. Even though myriad hybrid architectures exist, the ultimate objective of this proposal is to satisfy one intrinsic feature: incorporate superiority behavior of the hardwareassisted virtualization.
Keywords: virtual processor; hybrid processor; algorithm; virtualization; CPU machine